(untitled) (Global Scientific Review, 2023)
The article analyzes the sources of Alisher Navoi’s philosophical, mystical, moral views. The unique features of Nakshbandiyyah mystical teaching are revealed. The main focus is on research on the activity of the thinker. Alisher Navoi’s "Nasayim ul-Muhabbat" is researched for its superiority over other sources of Nakshbandi history written in Persian. Examples of Navoi’s thoughts on Nakshbandi doctrine ideas, procedures, manners are given.